Singing under glass: rapid effects of anthropogenic habitat modification on song and response behaviours in an isolated house sparrow Passer domesticus population. (14th March 2020) - Sheldon, Elizabeth L.; Ironside, Joseph E.; de Vere, Natasha; Marshall, Rupert C.
Abstract : Anthropogenic noise pollution and the introduction of novel infrastructure can impose strong selective pressures on avian communication by affecting the efficacy with which acoustic signals are transmitted and received. Many species have now been shown to sing at higher frequencies in noisy urban environments. However, few studies have investigated the effects of signal modification on the response behaviours of receivers, and fewer still have been able to indicate the timescale over which these changes in pitch have occurred. We compare vocal communication between house sparrows Passer domesticus that reside within the world's largest, single‐span glasshouse (completed in the year 2000), and house sparrows directly outside this glasshouse, in open farmland. The glasshouse contrasts both acoustically and physically with the external environment, low frequency background noise being significantly louder inside than outside. We show that minimum song frequency was significantly higher inside the glasshouse than in surrounding farm habitat. Using song playback, we also found that birds within the glasshouse reacted more strongly to playbacks from the glasshouse habitat than they did to playback of song from farm birds outside. The degree of difference in frequency is similar to that shown for other bird species between urban and rural environments, demonstrating that such behavioural differences may arise over a relatively short time period (14 yr in this case).